2015
DOI: 10.1179/1743286315y.0000000015
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of rock block size distribution for determination of Geological Strength Index (GSI) using discrete fracture networks (DFNs)

Abstract: Rock mass classification provides fundamental data for a numerical stability analysis of rock structures. Among rock mass classification systems, the RMR and Q systems often are used for rock support system selection and the Geological Strength Index (GSI) system for estimating rock mass strength and deformation parameters. Moreover, the GSI system is the only rock mass classification that is directly linked to engineering design parameters such as the Mohr-Coulomb or Hoek-Brown strength parameters or the rock… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The 3DEC was used here due to availability. The geometrical characteristics of discontinuities were adopted as the input properties; a series of discrete, planar, and disc-shaped discontinuities of finite size were created; and then, the cubic-shaped rock mass model was developed for block system generation [2,19,27,69,70].…”
Section: Pcm-sds: 3d Stochastic Dfn Simulationmentioning
confidence: 99%
See 2 more Smart Citations
“…The 3DEC was used here due to availability. The geometrical characteristics of discontinuities were adopted as the input properties; a series of discrete, planar, and disc-shaped discontinuities of finite size were created; and then, the cubic-shaped rock mass model was developed for block system generation [2,19,27,69,70].…”
Section: Pcm-sds: 3d Stochastic Dfn Simulationmentioning
confidence: 99%
“…Kluckner et al [70] introduced a boundary criterion for model size determination. Kim et al [69] arranged a virtual borehole extending through the model domain, and the model size was selected based on each discontinuity liner frequency. Macciotta et al [71] suggested that the model size could be assumed to be approximately four to five times the maximum fragment sizes (e.g., fragmented rockfall block sizes) surveyed in each dimension.…”
Section: Pcm-sds: 3d Stochastic Dfn Simulationmentioning
confidence: 99%
See 1 more Smart Citation
“…-For field data collection, several digital mapping techniques such as photogrammetry and laser scanning have been developed to improve the quality of data and minimize the time of data collection (Slob 2010;Assali et al 2014;Elmo et al 2014;Riquelme et al 2014;Kim et al 2015;Gaich et Pischinger 2016;Buyer et al 2018;Vazaios et al 2018;Li et al 2019;Buyer et al 2020;Azarafza et al 2021). Based on these techniques, a number of general methods for determining the rock blocks volume, have been proposed (Lopes et Lana 2017).…”
Section: Introductionmentioning
confidence: 99%